Assessing assessment: The Authorized Translator’s Examination in Finland - Marja Kivilehto; Leena Salmi (Department of Translators and Interpreters, Antwerp University, 2022)
The system for authorizing translators to translate legally valid texts used in Finland was revised in 2008 from a test measuring language skills into an examination containing translation assignments. The examination consists of two translation assignments and a test of the examinees’ knowledge of the professional practices of authorized translators (tested with multiple-choice questions). In the assessment of the translation products, a predefined two-dimensional assessment system is used in which translations are marked for both content and language quality. In this article, we discuss the assessment systems used in Finland, Sweden, Norway and Germany and present the results of a case study on the application of the scoring chart used in the Finnish examination.